The Effects of Prenatal Methamphetamine Exposure on Childhood Growth Patterns from Birth to 3 Years of Age - Zabaneh, Rachel; Smith, Lynne M.; LaGasse, Linda L.; Derauf, Chris; Newman, Elana; Shah, Rizwan; Arria, Amelia; Huestis, Marilyn; Haning, William; Strauss, Arthur; Grotta, Sheri Della; Dansereau, Lynne M.; Lin, Hai; Neal, Charles; Lester, Barry M. (American Journal of Perinatology, 2012)
We examined the effects of prenatal methamphetamine (MA) exposure on growth parameters from birth to age 3 years. The 412 subjects included (n = 204 exposed) were enrolled at birth in the Infant Development, Environment and Lifestyle study, a longitudinal study assessing the effects of prenatal MA exposure on childhood outcomes. Individual models were used to examine the effects of prenatal MA exposure on weight, head circumference, height, and weight-for-length growth trajectories. After adjusting for covariates, height trajectory was lower in the exposed versus the comparison children (p = 0.021) over the first 3 years of life. Both groups increased height on average by 2.27 cm per month by age 3 years. In term subjects, MA exposure was also associated with a lower height trajectory (p = 0.034), with both the exposed and comparison groups gaining 2.25 cm per month by age 3 years. There was no difference in weight, head circumference, or weight-for-length growth trajectories between the comparison and the exposed groups. Children exposed prenatally to MA have a modest decrease in height growth trajectory during the first 3 years of life with no observed difference in weight, head circumference, or weight-for-length trajectories.
Keywords: height; antenatal; drug; amphetamine